TANTANGAN GURU PAI DALAM PEMBENTUKAN AKHLAK ERA REVOLUSI INDUSTRI 4.0: LITERATURE REVIEW - Rokhmatul Khoiro Amin Putri; Asep Saepul Hamdani; Irma Soraya; Abdul Muhid (Universitas Islam Lamongan, 2023)
Progress in science and technology can be enjoyed by mankind, but on the other hand it has a negative impact on education, especially in the current millennial era which is very closely related to morals. Students experience many changes in attitude, they are used to the flow of information and industrial technology 4.0. Attitudes that emerge include gadget addiction, cyber bullying, or even a decline in morals or morals. So that it is appropriate for Islamic religious teachers to think about the right efforts in dealing with changes in the behavior of students in this 4.0 era. This study aims to reveal and explain the challenges faced by Islamic Religious Education teachers in the formation of student morals in the era of the industrial revolution 4.0. as well as the efforts made by the teacher in facing the challenges of moral formation. The method used in this study is a qualitative method using a library research approach. The results of this study are the challenges faced by PAI teachers in forming morals, namely a). The rapid development and progress of science and technology, b). Declining morals, manners, and behavior, c). Critical society, including crime, violence, unemployment d). Free trade rampant. Efforts made by teachers in facing challenges in the era of the industrial revolution 4.0 are a). Mastering the subject matter, science, information and technology that will be taught b). Reflects exemplary behavior and attitudes, c). Love and commitment to the profession, d). Mastering a variety of methods and strategies, e) Being open in the face of renewal and insight.